2017
DOI: 10.5607/en.2017.26.4.227
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory Effect of Glucagon Like Peptide-1 Receptor Agonist, Exendin-4, through Modulation of IB1/JIP1 Expression and JNK Signaling in Stroke

Abstract: Glucagon like peptide-1 (GLP-1) stimulates glucose-dependent insulin secretion. Dipeptidyl peptidase-4 (DPP-4) inhibitors, which block inactivation of GLP-1, are currently in clinical use for type 2 diabetes mellitus. Recently, GLP-1 has also been reported to have neuroprotective effects in cases of cerebral ischemia. We therefore investigated the neuroprotective effects of GLP-1 receptor (GLP-1R) agonist, exendin-4 (ex-4), after cerebral ischemia-reperfusion injury. Transient middle cerebral artery occlusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 49 publications
2
47
2
1
Order By: Relevance
“…COX-2 expression in ischemic tissue is quickly up-regulated after tMCAO together with MMP-2 and MMP-9 activity. Increased levels of COX-2 increase the level of prostaglandin E, with tissue destruction and early development of oedema (Kim et al, 2017). In our study, we found significantly higher COX-2-positive surface area in the penumbra than in the core.…”
Section: Discussionsupporting
confidence: 60%
“…COX-2 expression in ischemic tissue is quickly up-regulated after tMCAO together with MMP-2 and MMP-9 activity. Increased levels of COX-2 increase the level of prostaglandin E, with tissue destruction and early development of oedema (Kim et al, 2017). In our study, we found significantly higher COX-2-positive surface area in the penumbra than in the core.…”
Section: Discussionsupporting
confidence: 60%
“…Disuse-induced skeletal muscle atrophy is closely related to inflammatory process (Hunter et al, 2002). In addition, GLP-1based therapies have been shown to exert anti-inflammatory effects in chronic inflammatory diseases (Kim et al, 2017). We evaluated the expression of inflammatory cytokines and found that the mRNA levels of TNF-a, IL-1b, and IL-6 in the GA muscle were upregulated following 10 days from immobilization and that dulaglutide treatment inhibited this increase ( Figure 4A).…”
Section: Discussionmentioning
confidence: 97%
“…Excessive oxidative stress was also abolished by exenatide in the ischemic model of cardiac muscle injury (46). Noteworthy, it was also noted that excessive oxidative stress that occurred in rat model of cerebral stroke led to a significant reduction in the level of GLP-1 receptors (47). This loss might be at least partly compensated by the exogenously administered exenatide.…”
Section: Discussionmentioning
confidence: 99%